![image](https://tex.z-dn.net/?f=%28%5Cfrac%7B4%7D%7B9%7D+%2B+x%29+-+%5Cfrac%7B2%7D%7B9%7D+%3D+%5Cfrac%7B5%7D%7B9%7D+%5C%5C%0A%5Cfrac%7B4%7D%7B9%7D+%2B+%5Cfrac%7Bx%7D%7B1%7D+-+%5Cfrac%7B2%7D%7B9%7D+%3D+%5Cfrac%7B5%7D%7B9%7D+%5C%5C%0A%5Cfrac%7B4%7D%7B9%7D+%2B+%5Cfrac%7B9x%7D%7B9%7D+-+%5Cfrac%7B2%7D%7B9%7D+%3D+%5Cfrac%7B5%7D%7B9%7D+%5C%5C+%5C%5C%0A4+%2B+9x+-+2+%3D+5+%5C%5C%0A9x+%3D+5+-+4+%2B+2+%5C%5C%0A9x+%3D+3+%5C%5C%0Ax+%3D+%5Cfrac%7B9%7D%7B3%7D+%5C%5C%0Ax+%3D+3+%5C%5C+%5C%5C%0A%3Cstrong%3EOtvet%3A+x+%3D+3%3C%2Fstrong%3E)
Otvet: x = 3" alt="(\frac{4}{9} + x) - \frac{2}{9} = \frac{5}{9} \\
\frac{4}{9} + \frac{x}{1} - \frac{2}{9} = \frac{5}{9} \\
\frac{4}{9} + \frac{9x}{9} - \frac{2}{9} = \frac{5}{9} \\ \\
4 + 9x - 2 = 5 \\
9x = 5 - 4 + 2 \\
9x = 3 \\
x = \frac{9}{3} \\
x = 3 \\ \\
Otvet: x = 3" align="absmiddle" class="latex-formula">